Novel Technologies for Design and Analysis of Switching Mode Power-Supply Circuit Based on Solitary Electromagnetic Wave Theory. (4th March 2014) - Tohya, Hirokazu; Toya, Noritaka
Abstract : The novel solitary electromagnetic wave (SEMW) theory and the novel design methodologies of the switching mode power supply circuit (SMPC) are presented. The SEMW theory was developed as a basic theory of the design of all kinds of the switching mode circuit including SMPC by fusing the physics of semiconductor, nonlinear undulation, and electromagnetic wave. When the SEMW theory is used, the electromagnetic analysis of SMPC becomes possible by using only the real parameters based on the physics. The technologies of the low impedance lossy line (LILL) which is used to the DC line and the matched impedance lossy line (MILL) which is used to the switching line are also presented. They are effective for suppressing the electromagnetic interference. SMPC can be reconfigured to the quasistationary state closed circuit (QSCC) by applying LILL and MILL in accordance with the SEMW theory. No electromagnetic interference exist in QSCC. The buck converter which is one of the most popular DC-DC converters is presented as an example of the method for being reconfigured to QSCC. The conventional design tools which includes SPICE based on the AC circuit theory will be effective for the design and analysis of the inside circuit of QSCC.